FAKTOR MOTIVASI DAN INDIKATOR EKONOMI DALAM UJI KELAYAKAN JUSTICE COLLABORATOR - Iwan Lesmana; Dheny Biantara; Meco Sitardja (Universitas Agung Podomoro, 2021)
The purpose of this observation is to find the indicator of a person will meet the offering of being a justice collaborator. The population of this observation are the cases of person who is being suspected or accused by Komisi Pemberantasan Korupsi (KPK) commiting corruption in Indonesia. Participants for this study were sampled using the random sampling cases in observation, theory and the rules of law. Datas amd informations that were used for this observation were obtained through secondary data from cases in KPK’s website and the result of the previous research in motivation.Observation’s result indicates that age, education, experience, salary, job title and spiritual capital drive someone to be motivated. These factors do not act separately, but they are a part of mutually connected network of specific relations. Employee level of motivation and employee performance can be influenced by means of their detailed knowledge, esperience, maturity of thought and spiritual aspect.Economic indicators that was represented by the value of loss, value of gratification and the punishment charge can be considered in valuing somenone feasible become a justice collaborator. The final results of this observation are factors that affect motivation and economic indicators in court session might be used in measuring that someone would become a justice collaborator.